2020
DOI: 10.1111/joor.13124
|View full text |Cite
|
Sign up to set email alerts
|

Mandibular border movements: The two envelopes of motion

Abstract: Over the years, mandibular movements have been studied in dentistry to diagnose problems associated with masticatory function, for programming articulators for prosthetic restorations and for detecting temporomandibular joint alterations. 1 In many temporomandibular conditions, the ranges of mandibular movements are mainly decreased. Thus, clinical examination of mandibular motion becomes a relevant process in the functional evaluation of temporomandibular joints and a helpful indicator in diagnosis and treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 18 publications
(43 reference statements)
0
5
0
1
Order By: Relevance
“…These variables have been analyzed with different devices to try to overcome certain problems that arise when recording mandibular movement, head movement, faithful tracking of mandibular movement and modifying the natural movement during chewing. Border movements have been analyzed using EMA in several studies [19,38], and a new variable has been introduced by analyzing border movements eccentrically and concentrically [46], as well as through symmetry analysis [84]. In addition, it has been made possible to analyze masticatory kinematics, differentiation of each cycle and its stage of ascent and descent in the area described [52].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These variables have been analyzed with different devices to try to overcome certain problems that arise when recording mandibular movement, head movement, faithful tracking of mandibular movement and modifying the natural movement during chewing. Border movements have been analyzed using EMA in several studies [19,38], and a new variable has been introduced by analyzing border movements eccentrically and concentrically [46], as well as through symmetry analysis [84]. In addition, it has been made possible to analyze masticatory kinematics, differentiation of each cycle and its stage of ascent and descent in the area described [52].…”
Section: Discussionmentioning
confidence: 99%
“…Chuhuaicura et al [46] in their study on eccentric and concentric border movements, found significant differences in the described area concentrically and eccentrically from the frontal and sagittal polygons, with the area being greater concentrically in both cases. In this study, subjects were asked to perform border movements in the traditional way [41] and then in reverse, with a movement sensor attached to the interincisal line on the lower incisors.…”
Section: Area Of Posselt's Envelope Of Motionmentioning
confidence: 92%
See 1 more Smart Citation
“…If the link between tooth loss and cognitive impairment is confirmed, it will provide a novel means of targeting the prevention of cognitive impairment. Many clinical studies have shown that chewing exercise can be considered as a preventive method for cognitive impairment (Ono et al, 2010;Tada and Miura, 2017;Chuhuaicura et al, 2019). Corresponding results appeared after the use of implants or dentures to repair the missing teeth, patients' cognitive level can be improved (Ki et al, 2019;Tan et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…With electromagnetic articulography, kinematic analysis of the mandibular movement is possible, rather than static parameters. Thus, the aforementioned parameters can be recorded, and the trajectory described by the mandible from the start to the end point of the movement can also be observed [ 38 , 39 ]. This can open new perspectives on the diagnosis of the state of the TMJ since the trajectory and the form of the path of the mandible when performing the opening movement can be incorporated, both to analyze the maximum opening and the openings performed while chewing.…”
Section: Discussionmentioning
confidence: 99%